Hubungan Pengetahuan Ibu Hamil Dengan Kesiapsiagaan Menghadapi Bencana Kebakaran - Ilda Fitri; Siti Saleha; Zulfa Hanum (2025)
Knowledge and disaster preparedness in pregnant women need to be improved, because pregnant women are a group that is vulnerable to becoming victims during a disaster, one of which is the most frequent fire disaster. With the knowledge of pregnant women, preparedness in dealing with fire disasters can be formed and pregnant women can avoid the risks that may occur when pregnant women experience fire disasters. The purpose of this study was to determine the relationship between the knowledge of pregnant women with preparedness for fire disasters in the working area of the Lut Tawar Health Center in 2024. This type of research is quantitative with analytic type, using cross sectional approach. The population of this study were all pregnant women in the working area of the Lut Tawar Health Center, consisting of 73 samples taken by random sampling. Analysis of the results of the study was carried out using the chi square test. The results of the research analysis obtained a value of ρ = 0.000 (ρ < 0.05) so that there is a significant relationship between the two variables. It can be seen that there is a relationship between the knowledge of pregnant women and preparedness for fire disasters in the working area of the Lut Tawar Health Center in 2024. Thus the author concludes that if the knowledge of pregnant women is good, the level of preparedness in facing fire disasters will also be ready.